2009
DOI: 10.1177/1531003510365088
|View full text |Cite
|
Sign up to set email alerts
|

False Aneurysm of the Deep Femoral Artery as a Complication of Intertrochanteric Fracture of the Hip: Options of Open and Endovascular Repairs

Abstract: A quarter of all intertrochanteric fractures are unstable with a fractured lesser trochanter. Mostly these fractures are treated with a gamma nail fixation. A rare complication of this treatment is a false aneurysm of the femoral artery. The authors present 2 cases of a false aneurysm of the femoral artery in association with intertrochanteric fractures. Because of its nonspecific symptoms, a false aneurysm is difficult to diagnose. A computed tomography angiography or duplex should be used to confirm the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Recent studies have reported that the MFCA originates from the DFA in 65% and the CFA in 31–32% of cases [ 23 , 24 ]. In contrast, pseudoaneurysm of the DFA after the surgery is also reported [ 25 , 26 ]. Although pseudoaneurysm was caused by the fracture itself in some cases, operative fault such as guidewire migration was considered to be the main reason.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that the MFCA originates from the DFA in 65% and the CFA in 31–32% of cases [ 23 , 24 ]. In contrast, pseudoaneurysm of the DFA after the surgery is also reported [ 25 , 26 ]. Although pseudoaneurysm was caused by the fracture itself in some cases, operative fault such as guidewire migration was considered to be the main reason.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors defend that in cases of large pseudoaneurysms open surgery would be the treatment of choice, reserving endovascular techniques for smaller cases [10]. In cases in which the aneurysm is produced by the displacement of the LT, the definitive treatment would be achieved with the extraction of the bone fragment after the arterial ligature [10], although in these cases, endovascular treatment has been shown to be effective and without risk of recurrence, as in our case [7]. Endovascular treatments include Coils, Stents, coagulant agents, or combinations of them, without evidence recommending one technique over another in this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The particularity of the treatment performed is that we did not remove the shifted LT fragment. Other authors also performed endovascular treatments in cases of pseudoaneurysm due to displacement of the LT with satisfactory results without evidence of recurrence [1, 7, 8, 10]. The late onset of a pseudoaneurysm of the deep femoral artery or its branches is a rare complication after hip fractures, but it should be suspected in a clinical setting of persistent pain after nailing, together with the late onset of edema and hematoma in the thigh and indirect signs in radiographs, such as medial and superior displacement of the lesser trochanter or the calcified femoral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The latter scenario involves either injury of the DFA by a displaced bone fragment or damage by a trochanteric gamma nail or an interlocking screw. 3,4…”
Section: Discussionmentioning
confidence: 99%